An E-Delphi study to facilitate animal welfare assessment in Italian zoos and aquaria - Barbara de Mori; Elena Mercugliano; Adriana F. Cerizza; Pierfrancesco Biasetti; Daniela Florio; Riccardo Da Re; Sandro Mazzariol; Olga Usachova; Simone Basile; Claudia Gili; Sara Rota Nodari (PLoS ONE, 2025)
Ensuring animal welfare is a key aspect of animal management in zoological facilities and aquaria, representing a pivotal facet of their mission. Italy currently lacks a comprehensive and valuable assessment methodology for evaluating the welfare of captive animals. To address this gap, the present study aimed to identify the most important criteria that should be considered in the welfare management and assessment of animals housed in Italian zoos and aquaria. To pinpoint this issue, we engaged experts with diverse backgrounds, structuring their communication throughout an iterative process, by applying the Delphi methodology. A pilot and three Delphi rounds were administered online to 74 experts, asking them to a) validate relevant topics derived from current legislation and guidelines divided into three clusters: Care, Wellbeing, and Regulation; b) assess the relevance of these topics across taxonomic groups; c) propose and confirm indicators for each identified topic; d) suggest and refine a list of questions for animal welfare assessment. The results were three lists of questions, one for each cluster, with a total of 80 topics, 174 indicators, and 272 questions identified by the experts. The aspects included in these lists offer valuable insights into the main aspects experts consider relevant for captive animal welfare. Despite the complexity of animal welfare and the huge amount of species hosted in zoos limiting the possibility to cover this aspect with a single expert consultation, this project actively addresses the urgent need for standardization in animal welfare assessment, contributing to the ongoing development of zoological regulations in Italy. This is especially important given the current limited legislative framework, underscoring the link between animal welfare and successful ex-situ species conservation. These questions can be the basis of fine-tuned protocols to be tested in future projects aiming at animal welfare self-assessment, thus supporting authority inspection processes.